The Contribution of Executive Functions When Reading Multiple Texts: A Systematic Literature Review - Tarchi, Christian; Ruffini, Costanza; Pecini, Chiara (Frontiers in Psychology, 2021)
In the present-day knowledge society, people need to critically comprehend information across multiple sources that express diverse and contradictory viewpoints. Due to the complexity associated with this process, an important role can be played by Executive Functions, that is, cognitive control processes used to regulate mental functioning and behaviour when automatized elaborations are not sufficient. The aim of this article is to review existing research on the roles of executive functions when reading from multiple texts. To identify the appropriate studies, we conducted a search in the following databases: Web of science, Scopus, PsycInfo, Eric. The search string was created by combining the terms used in past literature reviews on executive functions and multiple-texts comprehension. From the total number of 4877 records identified, seven articles met all the inclusion criteria and were analyzed. Given the scarcity of studies on the topic, we decided to examine also eight articles reporting indirect evidence about the association between executive functions and multiple-text comprehension. Our review revealed that the study of the association between executive functions and multiple-texts comprehension is underdeveloped. The results seem to suggest that working memory is involved in surface comprehension, whereas results about sourcing and intertextual integration processes are mixed. Indirect evidence suggests that other executive functions, such as planning or monitoring, may be involved when learning from multiple texts. More research on this topic is needed given the increasing complexity of the contexts in which reading activities take place.